Prototypical clinical trial registry based on fast healthcare interoperability resources (FHIR): Design and implementation study - Gulden, Christian; Blasini, Romina; Nassirian, Azadeh; Stein, Alexandra; Altun, Fatma Betül; Kirchner, Melanie; Prokosch, Hans-Ulrich; Boeker, Martin (JMIR Medical Informatics, 2021)
Background: Clinical trial registries increase transparency in medical research by making information and results of planned, ongoing, and completed studies publicly available. However, the registration of clinical trials remains a time-consuming manual task complicated by the fact that the same studies often need to be registered in different registries with different data entry requirements and interfaces. Objective: This study investigates how Health Level 7 (HL7) Fast Healthcare Interoperability Resources (FHIR) may be used as a standardized format for exchanging and storing clinical trial records. Methods: We designed and prototypically implemented an open-source central trial registry containing records from university hospitals, which are automatically exported and updated by local study management systems. Results: We provided an architecture and implementation of a multisite clinical trials registry based on HL7 FHIR as a data storage and exchange format. Conclusions: The results show that FHIR resources establish a harmonized view of study information from heterogeneous sources by enabling automated data exchange between trial centers and central study registries.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Clinical trials; Data sharing; Health information interoperability; HL7 FHIR; Trials registry